A combination containing natural extracts of clove, Sophora flower bud, and yam improves fertility in aged female mice via multiple mechanisms - Liu, Wei; Wang, Xinyu; Chen, Yating; Zhang, Huiyu; Chen, Jing; Zhang, Jing; Wu, Tinghe; Li, Jing (Frontiers in Endocrinology, 2022)
Introduction With society development, the age at which women choose to have children has been gradually delayed. To improve the reduced fertility in women at advanced maternal age, we developed a combination containing natural extracts from clove, Sophora flower bud and Chinese yam with a mass ratio 15:6:10 and named it as DACHAO. Methods and Results We then gavage DACHAO at a dose of 310 mg/kg BW to female mice at 10 month of age and investigated its effects on ovarian functions. Using MitoTracker probes, ROS, and JC-1 staining, we found that DACHAO treatment improved mitochondria functions in oocytes from aged mice. We also observed increased blastocyst formation when mature oocytes from control and DACHAO treated mice were for IVF and in vitro embryo culture. Cell counting and TUNEL assay further revealed increased cell numbers and decreased apoptosis in blastocysts of DACHAO group. After control or DACHAO treated mice being mated with fertile male mice, fertility test revealed a greater first litter size in the DACHAO group. Further studies demonstrated that DACHAO treatment could alleviate the retarded ovarian function in aged mice via changes in serum hormone levels, over-expression of antioxidant factors, under-expression of inflammation-related factors, and reduced apoptosis in the ovaries. Discussion Thus, the new combination DACHAO will be a good choice in clinic to improve ovarian functions for women at advanced maternal age.